2023
DOI: 10.1007/s11111-023-00417-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social network sites usage in climate change awareness in Latin America

Abstract: Using data from the Latinobarómetro (Latin Barometer) survey of 2017 to analyze the effect of social network site usage on climate change awareness in 18 Latin American countries, this article makes three contributions. First, it offers results on the socioeconomic determinants of climate awareness in a region of the world where there is scant published evidence in this regard. Second, it shows the effect of social media consumption on climate change awareness by assessing the role of each of the most popular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 121 publications
0
0
0
Order By: Relevance
“…Our results align with prior studies, which indicated that the majority of respondents had satisfactory comprehension of the subject matter [8,9]. The rationale behind the surge in consciousness among young individuals and retirees in our analysis can potentially be attributed to the influence of social media and printed publications [10]. Recently, as a consequence of the presence of social media platforms and diverse campaigns, individuals have become cognizant of the issue of climate change and are amenable to altering their lifestyle choices to confront this environmental predicament.…”
Section: Awareness Of the Term Climate Change And Factors Affecting A...supporting
confidence: 91%
“…Our results align with prior studies, which indicated that the majority of respondents had satisfactory comprehension of the subject matter [8,9]. The rationale behind the surge in consciousness among young individuals and retirees in our analysis can potentially be attributed to the influence of social media and printed publications [10]. Recently, as a consequence of the presence of social media platforms and diverse campaigns, individuals have become cognizant of the issue of climate change and are amenable to altering their lifestyle choices to confront this environmental predicament.…”
Section: Awareness Of the Term Climate Change And Factors Affecting A...supporting
confidence: 91%